2017
DOI: 10.1177/2399654417713494
|View full text |Cite
|
Sign up to set email alerts
|

How effective is central enforcement? Evidence from convened committees in failing local authorities

Abstract: The recent economic slowdown has revealed weaknesses in existing fiscal arrangements and led to the reintroduction of enforcement mechanisms on local authorities within the OECD. One extreme intervention approach for municipalities in financial distress includes neutralization of the elected local leadership and its replacement with a convened committee. Yet how effective are such enforcement methods in the stabilization of local authorities? We present, for the first time, a complete empirical examination of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 72 publications
1
12
1
Order By: Relevance
“…Together with the Ministry of Interior, since the 2000s these ministries have adopted a strict approach toward local finances, especially toward municipalities that are less sound and marked by underperformance. However, they have granted more autonomy to a small group of local authorities demonstrating good performance (Reingewertz & Beeri, 2018).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Together with the Ministry of Interior, since the 2000s these ministries have adopted a strict approach toward local finances, especially toward municipalities that are less sound and marked by underperformance. However, they have granted more autonomy to a small group of local authorities demonstrating good performance (Reingewertz & Beeri, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…In 2003, the government declared that local deficits would no longer be covered automatically. Thus, in 2004, many local authorities faced a financial crisis: 76% of local authorities operated under deficits, over 50% activated recovery plans and 21% held back the wages of thousands of employees for months (Beeri & Yuval, 2013;Reingewertz & Beeri, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…In local government studies, the characteristics of the community as the context are of great importance (Beeri, Uster & Vigoda-Gadot, 2019). The consideration of socioeconomic and demographic characteristics such as the educational level of the community and its average income have become widespread in explaining the provision of both local goods and services at the local level (Beeri et al, 2018;De Borger & Kerstens, 1996;Loikkanen & Susiluoto, 2005;Milligan, Moretti & Oreopoulos, 2004). In fact, research has shown that the community's SES affects the local leader's capacity to govern (Howlett & Ramesh, 2015).…”
Section: The Moderating Effect Of the Socioeconomic Status Of The Loc...mentioning
confidence: 99%
“…Furthermore, four of these mergers were eventually dissolved. The resulting lack of trust in the local governments prompted senior government officials to abandon any hope of implementing this policy (Drew, Razin, and Andrews 2019;Reingewertz and Beeri 2018).…”
Section: Lack Of Reform In the Management Of Local Government In Israelmentioning
confidence: 99%
“…The central government, particularly the Ministry of Finance and the Ministry of the Interior, have traditionally taken a centralist and conservative view towards local authorities, both in routine times and during crises, sometimes even to the point of regarding the local economy as a threat to national economic stability (Beeri and Razin 2015;Blank 1994). Since the first decade of the 2000s, these ministries have become even stricter in how they deal with local financial crises (Beeri 2013;Reingewertz and Beeri 2018).…”
mentioning
confidence: 99%